PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEANRNING DALAM MENINGKATKAN KETERAMPILAN BERFIKIR KRITIS SISWA SMP NEGERI 52 SATAP HALMAHERA SELATAN - Tuara, Narilah A; Tasanif, Nurlaila H (Jurnal Pendidikan dan Ekonomi (JUPEK), 2025)
This study aims to improve students' critical thinking skills before implementing the discovery learning model. This type of research is a pre-experiment using a one-group pretest-posttest design. The design used consists of three stages, namely pretest, posttest, and treatment for six meetings. In this study, there are two variables, namely the independent variable and the dependent variable. The sample in this study was 38 students of class VIII of SMP Negeri 52 SATAP HAL-SEL in the 2025/2026 academic year who were determined by direct appointment techniques. The instrument used was a critical thinking skills test that met valid criteria of 25 questions, where the results of this study showed that in the pretest, students' critical thinking skills averaged 10.10 and the posttest average score was 16.25. With a normalized N-gain test of 0.45 or in the moderate category. Based on the results of the study above, it can be concluded that the critical thinking skills of class VIII students of SMP Negeri 52 SATAP HAL-SEL, through the application of the discovery learning model, have increased.